2019
DOI: 10.1108/jhom-09-2018-0267
|View full text |Cite
|
Sign up to set email alerts
|

A case-based methodology for lean implementation in hospital operations

Abstract: Purpose Although there are general methodologies for lean implementation in manufacturing companies, a specific methodology for the implementation of lean healthcare in hospitals has not been addressed by the literature. Addressing this gap, the purpose of this paper is to develop a practice-driven methodology for implementing lean in hospital operations. Design/methodology/approach Three case studies were conducted to collect evidence on the lean implementation process in Brazilian hospitals. From empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…The applicability of lean thinking has been proven in the literature by hundreds of successful case studies, such as in banking sector (Hidayati, Tarigan and Tarigan, 2019), construction (Li, Fang and Wu, 2020), pharmaceuticals (Sieckmann et al, 2018), electronics (Nguyen and Do, 2016), services (Piercy and Rich, 2009), metallurgy (Ching, Hoe, Hong, Ghobakhloo, in Pin, 2015), shipbuilding (Sharma and Gandhi, 2017), health (Régis, Santos and Gohr, 2019), as well as its implementation in universities (Balzer et al, 2016) where all these sectors have demonstrated the applicability and adaptability of the Lean concept. Its implementation has also been linked and integrated with other concepts, services or paradigms.…”
Section: Lean Manufacturing Implementationmentioning
confidence: 99%
“…The applicability of lean thinking has been proven in the literature by hundreds of successful case studies, such as in banking sector (Hidayati, Tarigan and Tarigan, 2019), construction (Li, Fang and Wu, 2020), pharmaceuticals (Sieckmann et al, 2018), electronics (Nguyen and Do, 2016), services (Piercy and Rich, 2009), metallurgy (Ching, Hoe, Hong, Ghobakhloo, in Pin, 2015), shipbuilding (Sharma and Gandhi, 2017), health (Régis, Santos and Gohr, 2019), as well as its implementation in universities (Balzer et al, 2016) where all these sectors have demonstrated the applicability and adaptability of the Lean concept. Its implementation has also been linked and integrated with other concepts, services or paradigms.…”
Section: Lean Manufacturing Implementationmentioning
confidence: 99%
“…Change causes high pressures in carrying out hospital operations (Hugh, Gliebe & Sendlhofer, 2019). Other problems are also faced by management which due to the employees who are resistant to change (Regis, Santos & Gohr, 2019).…”
Section: "A Simple Example Is the Use Of A Tissue To Wash Your Hands mentioning
confidence: 99%
“…In manufacturing, it is possible to observe systematic methodologies for the application of Lean (Karim and Arif-Uz-Zaman, 2013); however, in the literature, a standardized system was not identified to the health service, as described in Régis et al . (2019).…”
Section: Introductionmentioning
confidence: 99%